Application of NPE in the assessment of a patent ductus arteriosus. (July 2018) - van Laere, David; van Overmeire, Bart; Gupta, Samir; El Khuffash, Afif; Savoia, Marilena; McNamara, Patrick; Schwarz, Christoph; de Boode, Willem
Abstract In many preterm infants, the ductus arteriosus remains patent beyond the first few days of life. This prolonged patency is associated with numerous adverse outcomes, but the extent to which these adverse outcomes are attributable to the hemodynamic consequences of ductal patency, if at all, has not been established. Different treatment strategies have failed to improve short-term outcomes, with a paucity of data on the correct diagnostic and pathophysiological assessment of the patent ductus arteriosus (PDA) in association with long-term outcomes. Echocardiography is the selected method of choice for detecting a PDA, assessing the impact on the preterm circulation and monitoring treatment response. PDA in a preterm infant can result in pulmonary overcirculation and systemic hypoperfusion, Therefore, echocardiographic assessment should include evaluation of PDA characteristics, indices of pulmonary overcirculation with left heart loading conditions, and indices of systemic hypoperfusion. In this review, we provide an evidence-based overview of the current and emerging ultrasound measurements available to identify and monitor a PDA in the preterm infant. We offer indications and limitations for using Neonatologist Performed Echocardiography to optimize the management of a neonate with a PDA.